Desenvolvimento e validação de método para determinação de etilenotiouréia em urina empregando HPLC UV - Vareli, Catiucia Souza (2008)
In order to supply the world-wilde demand for food, it is essential to use the pesticides to protect the crops against pests and diseases. But the indiscriminate and injudicious use of these compounds have resulted in widespread contamination in food commodities and environment in all fields, increasing, this way, the preoccupation with chemical products use. Ethylene-bis-dithiocarbamate pesticides, from dithiocarbamate class, are among the most widely used fungicide to control pest. Beside their low toxicity, one of they degradation products, ethylenethiourea, is a toxic metabolite, which have teratogenic, carcinogenic, immunotoxic and mutagenic effects. In the present work, it was developed and validated a chromatographic method for the determination of ethylenethiourea (ETU) residues in urine, using liquid-liquid extraction and HPLC quantification. The developed procedure consist of the interested compound extraction from urine, with 6.0 mL of dichloromethane, aditioning MgSO4 to help in the partitioning process, that is, distribution os compound between organic and aqueous phase. After sample centrifugation, a supernatant aliquot was taken and evaporated, in water bath at 44 ºC, and the final extract was redissolved in purified water and analyzed by HPLC-UV, injecting 50 μL in C18 column with mobile phase MeOH:H2O (10:90; v/v) and detection by UV light absorption at 233 nm. To the validation study of the method, the following parameters were evaluated: detection limit (LOD), quantification limit (LOQ), precision (under repeatability and reproducibility conditions) and accuracy as recovery. The method LOD was 0.05 mg ETU L-1 and LOQ was 0.2 mg ETU L-1. The analytical curve was linear between 0.05 to 1.0 mg ETU L-1 with determination coefficient r2 > 0.998. Very good precision with RSD between 1.7 and 2.7% was obtained and the recoveries ranged from 85.6 to 95.4% for 3 different spike level: 0,05, 0,1 and 0,5 mg ETU L-1 . The results obtained in the validation step allow us to conclude that the method are quite appropriate to determine residue of ethylenethiourea in urine. The developed method has shown advantages, such as simplicity, quickness and that it could be applied in any laboratory. However, there are some points such as no ETU confirmation nether purity analysis of the chromatographic picks besides the low sensitivity and selectivity of the UV detection that would be much improved using a LC-MS/MS.